Consolidation of sanitary and medico-legal offices, and abolition of coroners' courts - Mapother, E. D. (Statistical and Social Inquiry Society of Ireland, 1869)
I propose to comment very briefly on the provisions made by the State for the prevention of disease, the collection of mortuary statistics, and for the conduct of medico-legal enquiries. They seem to me to be less perfectly organized and less successful than those of many continental and American states.
Read, Tuesday, 12th May, 1868
Keywords: Health policy in Ireland; Coroners courts; Disease prevention policy; Medico-legal institutions in Ireland; 314.15